Intelligent Foot Insole: Real Time Gait Pattern Analysis and Performance Optimization (International Journal of Engineering & Extended Technologies Research (IJEETR), 2026)
This project presents the design and development of an intelligent foot insole system for real-time gait analysis. The system uses embedded sensors such as force sensors, flex sensors, and an MPU6050 accelerometer to monitor walking patterns. These sensors continuously collect data related to pressure distribution, movement, and orientation of the foot. The collected data is processed using an Arduino Nano microcontroller for analysis. The system helps in detecting abnormalities like gait asymmetry, imbalance, and drop foot conditions. It provides real-time alerts using a buzzer to notify the user or caregiver. The data can also be monitored using a PC for further analysis. This system is especially useful for elderly people and rehabilitation patients. It is low-cost, wearable, and easy to use. Overall, it improves safety and supports preventive healthcare.
Keywords: Arduino ide Iot; pressure sensor; low cost; real time monitoring